ON THE QUESTION OF TEACHING PASSIVE VOCABULARY JUNIOR SCHOOLCHILDREN (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the using of passive grammar in the process of foreign teaching reading. The principles o f junior schoolmates passive lexic teaching are elaborated and the interaction between teacher and pupils during its studying is represented.